STRATEGI DAN PARTISIPASI PENGEMBANGAN KAMPUNG ADAT SEGUNUNG: Studi Kasus Ds. Carangwulung Kec. Wonosalan Kab. Jombang - Kusumastuty, Ria; Wijaya, Dian; Sidharta Arisandi, Rachman (MAJAPAHIT POLICY, 2023)
The concept of village government according to Law no. 6 of 2014 and emphasis on efforts to empower internal villagesimprove the quality of life of rural communities. Apart from that, it explained the village innovation program initiated by the Regency GovernmentJombang, especially the Village Innovation Exchange (BID) which aims to improve the village economy through developing local potential. Then,presented about community-based tourism development strategies and the importance of community involvement in developing objects andtourist destination area (ODTW)